Actualization of Charity Verses in the Living Qur’an Perspective in the Friday Blessings Program - Syaiful Nazaar; Sugeng Wanto; Nur Aisyah Simamora (IJoIS: Indonesian Journal of Islamic Studies, 2026)
One of the Islamic teachings that offers solutions to the problems of poverty and destitution is zakat, infaq, and sadaqah. Zakat, which is the third pillar of Islam, functions to distribute wealth from those who are obligated to pay it (muzakki) to those who are entitled to receive it (mustahik). However, in this study, the researcher focuses specifically on the topic of sadaqah (charity). Based on this phenomenon, the researcher is motivated to further examine the Actualization of Charity Verses from the Perspective of the Living Qur’an in the Friday Blessings Program. This study is expected to provide a more comprehensive understanding of charity verses through the Living Qur’an approach, so that the Qur’an can be understood as a living source of values that remains relevant in the socio-religious practices of society. Based on the research findings and discussion, it can be concluded that the implementation of Qur’anic charity verses through the Friday Blessings Program demonstrates that the teachings of charity are not merely normative, but also possess a strong practical dimension in social life. First, the Qur’anic verses on charity emphasize sincerity, social concern, and the promise of multiplied rewards. Second, the motivation of donors and volunteers in practicing charity is dominated by spiritual awareness, particularly the desire to attain the pleasure of Allah. Third, the implementation of charity verses in the Friday Blessings Program provides multidimensional benefits. Fourth, from the perspective of the Living Qur’an, the Friday Blessings Program shows that Qur’anic verses can be actualized in dynamic social practices. Fifth, critically, this study finds that the implementation of charity in the program still has limitations, such as the dominance of consumptive aid patterns, unsustainable social relations, and practices that may be carried out routinely without deep reflection.